575 Are More Patients Being Harmed Than Treated with VTE Prophylaxis in Plastic Surgery? A Single-Centre Cycled Audit Reviewing Prescribing Practices. (19th August 2022) - Kazzazi, F; McKean, A; Magill, H; Noton, T; Mitchell, C; Jatan, A
Abstract: Aim: Venous thromboembolism prophylaxis (VTEP) was introduced following research showing that it was successful at preventing thrombotic complications in surgery patients. However, recent evidence demonstrates that patients in this cohort had subclinical venous thromboembolic disease and the benefit of VTEP was over-estimated. The Number Needed to Harm (NNH) is 26–67 while the Number Needed to Treat (NNT) is 147. This retrospective analysis attempted to identify if incorrect prescriptions in patients undergoing plastic surgery was possibly causing greater harm in a single plastic surgery centre. Method: A retrospective analysis of the notes of all admissions in 1 month was conducted. VTEP forms and prescriptions were reviewed and compared against recommendations from the National Institute for Health and Care Excellence as well as local policy. A teaching session was delivered to explain to the department issues with prescriptions, then another 1 month of notes were analysed. Results: 54 patients assessed in first round. Incongruence between prescriptions and recommendations identified in 40%. Using the month assessed to extrapolate for the year, correct prescriptions led to 1 avoidable major VTE per year. Incorrect prescription led to between 2 and 6 avoidable bleeds per year. Following intervention, there was no significant difference in accuracy in later month assessed (45 patients). People interviewed felt it was safer to prescribe VTEP despite evidence. Conclusion: There was an over-prescription of VTEP in plastic surgery patients in our cohort leading to a potential greater number of harmed than treated patients. This may require an attitude change towards VTEP to reduce patient harm.